Application of Nanoscience in Self-cleaning Properties of Concrete Facade for Development of Sustainable Environment - Seyedeh Fatemeh Khoshkalam Soleimandarabi; Raheleh Rostami; Mehdi Nezhadnaderi (Anthropogenic Pollution)
Using mineral admixtures in cement composites as a way to improve their mechanical and sustainable environmental properties is a common practice in concrete technology. Among them nano-silica effectively influences the composite's early and long-term properties. In this study, the effect of different percentages of TiO2 (0, 2.5 and 5 %) on self-cleaning properties and water absorption of cement composites containing nano-silica were investigated. according to the use of different cementitious material (nano-silica) and TiO2 in mix proportions, to obtain mixtures with a desirable workability, superplasticizer was added in different volume percentages.Better size distribution and pore refinement lead to a denser cement matrix with low porosity which in turn considerably lower the water absorption of the cement composites. the maximum final water absorption according to ASTM C497 is 9% for method A and 8.5% for method B. Comparsions of water absorption tests as a result of adding of TiO2 and nano-silica in concrete show that the maximum final water absorption is 4.9% in N1 design mixture and the minimum final water absorption is 4.3% in N2 design mixture.The incorporation of TiO2 has positively affected the results for nano-silica containing specimens. A decrease of 6.5% and 11.1% between N1 and N3 respectively shows the positive effect of TiO2 on decrease of water absorption. The results show that TiO2 along with nanosilica has great potential for improving the environmental and self- cleaning properties of concrete facades of buildings in cities exposed to high levels of cleanliness.